Components in Lentinus edodes mushroom with anti-biofilm activity directed against bacteria involved in caries and gingivitis. Issue 6 (8th June 2018) - Papetti, Adele; Signoretto, Caterina; Spratt, David A.; Pratten, Jonathan; Lingström, Peter; Zaura, Egija; Ofek, Itzhak; Wilson, Michael; Pruzzo, Carla; Gazzani, Gabriella
Abstract : The present study investigated the compounds present in the low molecular mass fraction of Lentinus edodes mushroom (shiitake) extract and their anti-virulence activity against oral pathogens. Abstract : The present study investigated the compounds present in the low molecular mass fraction of Lentinus edodes mushroom (shiitake) extract and their anti-virulence activity against oral pathogens (reference and clinical Streptococcus mutans, Actinomyces naeslundii, and Prevotella intermedia strains). Oxalic, succinic, and quinic acids, and adenine, inosine, and uridine were identified by HPLC-DAD-ESI-MS/MS. Their anti-biofilm production and preformed biofilm disaggregation activities were studied using commercial standard compounds at different concentrations. As regards S. mutans, the highest activity was shown by adenine at 5 mg mL −1 both in the biofilm inhibition (BI 50%) and biofilm disaggregation tests (BD 20%). Considering A. naeslundii, BI values close to 80% were registered for oxalic acid at 1 mg mL −1 and 2 mg mL −1 and BD 50% for quinic acid at 3 mg mL −1 . A weaker activity was found against P. intermedia . Furthermore, different mixtures of the commercial standards were tested showing that the activity of a compound can be strongly and sometimes negatively affected by the presence of the other compounds.